Identification and Validation of ATF3 Serving as a Potential Biomarker and Correlating With Pharmacotherapy Response and Immune Infiltration Characteristics in Rheumatoid Arthritis - Hu, Huan; Zhang, Facai; Li, Li; Liu, Jun; Ao, Qin; Li, Ping; Zeng, Jiashun; Li, Long (Frontiers in Molecular Biosciences, 2021)
Background: Although disease modifying anti-rheumatic drugs (DMARDs) have significantly improved the prognosis of patients with rheumatoid arthritis (RA), approximately 40% of RA patients had limited response. Therefore, it was essential to explore new biomarkers to improve the therapeutic effects of RA. This study aimed to develop a new biomarker and validate it in vitro study. Methods: We downloaded the RNA-seq and the clinicopathologic data of RA patients from Gene Expression Omnibus (GEO) databases. Differentially expressed genes were screened in the GPL96 and GPL570 databases. Then, weighted gene co-expression network analysis (WGCNA) was used to explore the most correlated gene modules to normal and RA synovium in the GPL96 and GPL570 databases. After that, we intersected the differentially expressed genes with the correlated gene modules to find out the potential biomarkers. The CIBERSORT tool was applied to investigate the relationship between the ATF3 expression and the immune cells infiltration, and Gene set enrichment analysis (GSEA) was used to investigate the related signaling pathways of differentially expressed genes in high- and low ATF3 groups. Furthermore, we also explored the relationships between ATF3 expression and clinical parameters in GEO database. Finally, we verified the role of ATF3 in vitro cell experiments. Results: We intersected the differentially expressed genes and most correlated gene modules in the GPL570 and GPL96 databases and identified that ATF3 was a significant potential biomarker and correlated with some clinical-pharmacological variables. Immune infiltration analysis showed that activated mast cells had a significant infiltration in the high ATF3 group in the two databases. Gene Set Enrichment Analysis (GSEA) showed that metabolism associated pathways belonged to the high ATF3 groups and inflammation and immunoregulation pathways were enriched into the low ATF3 group. Finally, we validated ATF3 could promote the proliferation, migration and invasion of RA-FLS and MH7A. Flow cytometry showed that ATF3 expression could decrease the proportion of apoptosis cell and increase the proportion of S and G2/M phase cells. Conclusion: We successfully identified and validated that ATF3 could serve as a novel biomarker in RA, which correlated with pharmacotherapy response, immune cell infiltration.